2012
DOI: 10.1039/c2dt12126c
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations

Abstract: An effective anion sensor, [Ru(II)(bpy)(2)(H(2)L(-))](+) (1(+)), based on a redox and photoactive {Ru(II)(bpy)(2)} moiety and a new ligand (H(3)L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F(-)) and acetate (OAc(-)) ions. Crystal structures of the free ligand, H(3)L and [1](ClO(4)) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO(4)) shows that the benzimidazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…The Os1-N1(imidazole) and Os1-O1-(carboxylate) bond lengths involving HL 2− in 1 of 2.059(2) Å and 2.116(18) Å, respectively, are close to the earlier reported Ru-N(imidazole): 2.049(5) Å/2.054(4) Å and Ru-O(carboxylate): 2.102(4) Å/2.103(3) Å bond lengths for the corresponding [Ru II (bpy) 2 (H 2 L − )]ClO 4 /[Ru II (bpy) 2 (HL 2− )], respectively. 13 The Os1-N1(imidazole) and Os1-O1(carboxylate) bond lengths in 1 also match well with the reported {Os II (bpy) 2 } complexes incorporating a partially deprotonated 4,5-bis(benzimidazol-2-yl) imidazole ligand. 17 The average Os-N(bpy) bond length of 2.038(8) Å in 1 matches reasonably well with the reported distances in the analogous complexes.…”
Section: Dalton Transactions Papersupporting
confidence: 83%
See 2 more Smart Citations
“…The Os1-N1(imidazole) and Os1-O1-(carboxylate) bond lengths involving HL 2− in 1 of 2.059(2) Å and 2.116(18) Å, respectively, are close to the earlier reported Ru-N(imidazole): 2.049(5) Å/2.054(4) Å and Ru-O(carboxylate): 2.102(4) Å/2.103(3) Å bond lengths for the corresponding [Ru II (bpy) 2 (H 2 L − )]ClO 4 /[Ru II (bpy) 2 (HL 2− )], respectively. 13 The Os1-N1(imidazole) and Os1-O1(carboxylate) bond lengths in 1 also match well with the reported {Os II (bpy) 2 } complexes incorporating a partially deprotonated 4,5-bis(benzimidazol-2-yl) imidazole ligand. 17 The average Os-N(bpy) bond length of 2.038(8) Å in 1 matches reasonably well with the reported distances in the analogous complexes.…”
Section: Dalton Transactions Papersupporting
confidence: 83%
“…14, 1266.89 and 1330. at 1625 cm −1 , 1621 cm −1 and 1619 cm −1 , respectively, are close to that of the free ligand (H 3 L) value of 1627 cm −1 . 13 The ν(ClO 4 ) frequencies of [2](ClO 4 ) 2 appear at 1100 cm −1 and 600 cm −1 . The expected N-H vibration of the coordinated HL 2− in the complexes could not be clearly identified, due to the presence of a broad water peak (KBr disk) around the region of 3500-3300 cm −1 .…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study revealed that the anion sensing mechanism was mediated by hydrogen bonds. The free N‐H group in benzimidazole could form hydrogen bonds with the pendant carboxylate oxygen while the imidazole N‐H was responsible for possible hydrogen‐bond interaction with the anions . It has been found that transition metals can be used as structural elements to build up anion receptors, enhancing hydrogen‐bond donor tendencies and favoring the assembling of the molecular framework.…”
Section: Imidazoles As Diagnostic Agents and Pathologic Probesmentioning
confidence: 99%
“…They are used as light harvesters in dye-sensitized solar cells [2][3][4], luminescent emitters in light-emitting electrochemical cells [5][6][7], potential anticancer and imaging agents in phototherapy [8][9][10], sensors for ions [11][12][13][14][15][16] and small molecules [17,18], photocatalysts for water splitting [19,20], hydrogen production [21][22][23][24], CO 2 reduction [21,23,25], and many other chemical reactions [23,[26][27][28][29], components in mixed valence systems [30][31][32][33][34][35], light upconversion systems [36][37][38][39] and molecular memory devices [40][41][42].…”
Section: Synthesis and Characterization Of Ruthenium(ii) Complexes Inmentioning
confidence: 99%